PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019) - Linvia Fitria; Moch. Dzulkirom AR (Fakultas Ilmu Administrasi Universitas Brawijaya, 2020)
The study investigated the effect of Capital Structure Influence on Company Profitability of Banking Sub Sectors listed on the Indonesia Stock Exchange for the 2016-2019 Period. This research uses value based measures in the form of Debt Ratio (DR), Debt to Equity Ratio (DER), and Time Interest Earned Ratio (TIER), and profitability ratios in the form of Return on Equity (ROE) and Return On Assets (ROA) for the analysis material. The approach of this research is quantitative with explanatory methods. The population in this research were 44 banking sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2019 period with a sample of 11 companies determined using the purposive sampling method. This research uses value based measures in the form of Debt Ratio (DR), Debt to Equity Ratio (DER), and Time Interest Earned Ratio (TIER), and profitability ratios in the form of Return on Equity (ROE) and Return On Assets (ROA) for the analysis material. Analysis of the data used in this research were descriptive statistics, classic assumption tests, multiple linear regression analysis, coefficient of determination tests and hypothesis tests. The results of hypothesis 1 indicated DR and DER partially had a negative and insignificant effect on ROE while TIER partially had a positive and significant effect on ROE. The results of hypothesis 2 indicated DR partially has a negative and insignificant effect on ROA while DER and TIER partially has a positive and significant effect on ROA. Keywords : Debt Ratio, Debt to Equity Ratio, Time Interest Earned Ratio, Return On Equit, and Return On Assets